An NMR relaxometry study of heteronuclear effects upon proton transfer in hydrogen bonds - Frantsuzov, Ilya (2010)
The inherent quantum-mechanical nature of the proton transfer process in hydrogen bonds has been investigated through its effects on the nuclear spin-lattice relaxation rate. The fast magnetic field-cycling techniques employed allowed a direct measure of the rate characterising this dynamic process, which is closely related to the potential energy environment experienced by the mobile proton.